STRATEGI PENGELOLAAN ZAKAT DALAM UPAYA PENGEMBANGKAN USAHA PRODUKTIF (Studi Kasus Pada BAZNAS Kabupaten Bungo) - Muklisin, Muklisin (JURIS (Jurnal Ilmiah Syariah), 2018)
Zakat management is an activity of planning, organizing, implementing, and supervising the collection, distribution, and utilization of zakat. Zakat management is carried out by Amil Zakat Agency formed by the government which is organized in the form of an agency or institution. The management system of Amil Zakat Agency (BAZNAS), as a zakat management institution established by the government, is still not optimal and less trusted by the public or muzakki. This means that the performance still needs to be improved to maintain the continuity of the benefits of the use of zakat and infaq. Therefore, BAZNAS must be able to make a strategy in managing zakat, especially in developing productive businesses so that it can provide and help the productive businesses for citizens so they can develop the economy of their own family.